Astrophysics at the Garbasso - Romoli, Marco; Salvadori, Stefania (Il Colle di Galileo, 2022)
The Garbasso building was home to the Department of Astronomy and Space Science for about 10 years, from 2002, and still hosts researchers and lecturers from the astrophysics group of the Department of Physics and Astrophysics who work in various areas of research, from the Sun to exoplanets, from astrophysical plasma to cosmology.